2003
DOI: 10.1034/j.1600-0501.2003.140202.x
|View full text |Cite
|
Sign up to set email alerts
|

Instrument for extraction socket measurement in immediate implant installation

Abstract: The aim of the present study was to create an instrument and a computer program for measurement of extraction sockets and for planning of the immediate replacement of teeth using screw-shaped dental implants. Ten titanium screw-shaped Osteofix Dental Implant System implants (Osteofix, Oulu, Finland) were immediately installed after extraction in nine patients, four women and five men (age 17-62 years). The measurements of fresh extraction sockets were taken at six points (mesio-buccal, buccal, disto-buccal, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…In the process of the fixture installation, it is also important to get enough primary stability 14. Because implant success rate increases as the primary stability increases, thereby showing better prognosis 15.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of the fixture installation, it is also important to get enough primary stability 14. Because implant success rate increases as the primary stability increases, thereby showing better prognosis 15.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, within the last decades, the 'gold standard' implant treatment protocol has been challenged by experiments, which aimed at shortening the treatment period and by reducing the number of surgical procedures. The literature has demonstrated that it is no longer needed to wait for complete healing of the extraction socket before implant placement (Lazarra 1989;Knox et al 1991;Lundgren et al 1992 Wilson et al 1998;Rosenquist & Ahmed 2000;Hämmerle & Lang 2001;Nemcovsky et al 2002;Juodzbalys 2003;Bianchi & Sanfilippo 2004). With this surgical approach, it allows a better final rehabilitation because it facilitates morphological ridge contour preservation as well as accurate prosthetic implant installationmaintaining the natural tooth angle (Werbitt & Goldberg 1992).…”
mentioning
confidence: 99%
“…However, evidence has shown no need for complete healing of the socket and that both tooth extraction and implant placement can be successfully performed in a single surgical procedure (Rosenquist & Ahmed ; Covani et al. ; Juodzbalys ; Schropp et al. ).…”
mentioning
confidence: 99%
“…Branemark's (1985) original protocol recommended a 6-month waiting period between tooth extraction and implant placement (Covani et al 2003) as a prerequisite for osseointegration of the implant (Rosenquist & Ahmed 2000). However, evidence has shown no need for complete healing of the socket and that both tooth extraction and implant placement can be successfully performed in a single surgical procedure (Rosenquist & Ahmed 2000;Covani et al 2003;Juodzbalys 2003;Schropp et al 2005). Although the immediate implantation technique (Schulte et al 1978) has been studied with animals (Botticelli et al 2004a; and humans (Paolantonio et al 2001;Covani et al 2003), few studies have evaluated it in molar regions.…”
mentioning
confidence: 99%